Treatment of lower extremity oedema by subcutaneous drainage in a home hospice patient. (29th April 2013) - Rodgers, Susan; Birkholz, Lorri; Hebert, Randy
Abstract : Lower extremity oedema is common in patients with advanced illness and can normally be managed with oral diuretics and elevation of the involved extremities. The management of oedema can be more complicated in home hospice patients, however. They tend to be more frail and are often less able to tolerate usual interventions. We present a case of a home hospice patient with severe oedema treated by creating subcutaneous tracts in his legs to allow drainage of excess interstitial fluid. The procedure was very successful in improving the patient's quality of life.